On Running and Becoming Human An Anthropological Perspective - Carter, Thomas F. (Springer International Publishing, 2018)
How does the simple act of running make us human? As a form of enskilled movement that shapes how we perceive our surroundings, running enacts a mindful bodily engagement with the world, an engagement that generates our very minds through perceptual learning. Thomas F. Carter examines the interrelated aspects of a runner's being-mind, body, and environs-to illustrate that the skillful act of locomotion is one of principle ways that we as human beings become integral parts of the larger world. Synthesizing recent developments in neuroscience, anthropology, and philosophy of mind, On Running proves there is more to running than merely clocking up the miles.